Growing together: Croatia and Latvia - Thorvaldur Gylfason; Eduard Hochreiter (Center for Economic Studies and ifo Institute (CESifo), 2010)
We compare and contrast the economic growth performance of Croatia and Latvia since the collapse of communism in 1991 in an attempt to understand better the extent to which the growth differential between the two countries can be traced to increased efficiency in the use of capital and other resources (intensive growth) as opposed to sheer accumulation of capital (extensive growth). On the basis of a simple growth accounting model, we infer that advances in education at all levels, good governance, and institutional reforms have played a significant role in raising economic output and efficiency in both Croatia and Latvia. The EU perspective made a more significant contribution to growth in Latvia than in Croatia, even if Latvia's immediate post-accession boom proved unsustainable.
Keywords: O16; 330; economic growth; governance; transition economies; Wirtschaftswachstum; Übergangswirtschaft; Bildungsinvestition; Good Governance; Institutioneller Wandel; Schätzung; Vergleich; Lettland; Kroatien